Potentialities of Artificial Intelligence in Higher Education: An Approach from Personalization (Docentes 2.0 Journal, 2022)
There is a significant interest in knowing the educational processes and their actors in the case of research in the academic and pedagogical fields. The objective of this study was to analyze the potential of AI tools in higher education, taking into account an approach from the personalization of learning. This research was conducted under the empirical-analytical method, positivist paradigm, exploratory type, and documentary design. The population or sample considered were four databases (Scopus, Web of Science (Wos), Dialnet, and Redalyc). The technique used was a documentary observation, and the instrument used was the content sheet. The data analysis was carried out through the analysis matrix of the categories. The documents that did not answer the research questions proposed for this review were filtered with Boolean operators. In light of the results obtained, it is essential to consider the importance of contrasting pedagogical and curricular models concerning personalization. It is important to remember that a system with high technical content but little pedagogical content will deter students from using it. As a contribution to future research, it is recommended to consider the pedagogical and curricular models in the construction of personalization models. In addition, a contract should be made between the methodologies available in the literature to assess strengths and weaknesses.
Keywords: Artificial intelligence; higher education; personalization